Fulminant corporal infection induced by Fournier gangrene: A case report with unusual presentation - Sultan S. Almaiman (Elsevier, 2022)
Fournier gangrene is a life-threatening surgical emergency caused by multiple infectious organism usually affecting the subcutaneous perineal, genital or perianal region with high incidence in immunocompromised patients.In very rare situations such our case when it involves the Deep perineal fascia and invading into the corporal body, the necrotizing tissue spread and control becomes more challenging and lead into devastating events with high mortality rate.Staged timely debridement with highly daily examination to rule out necrosis spread is highly recommended.